IMPACT ANALYSIS OF CHINA'S ELECTRIC VEHICLE DISTRIBUTION ON CULTURAL IDENTITY JAKARTA SOCIETY - Kuswardani, Suci; Lawanda, Ike Iswary (International Review of Humanities Studies, 2025)
This study examines the impact of China's electric vehicle distribution on the cultural identity of Jakartans. With increasing air pollution and congestion in the capital city, electric vehicles have emerged as a sustainable transportation solution. This study uses a qualitative approach with data collection through interviews with 5 sources of information, namely Mr. Susanto, Mr. Robert, Mrs. Astrid, Mrs. Ratna and Mrs. Jeane. This was done to understand the adoption of electric vehicles affecting social values, cultural interactions, and community mobility patterns. The results of the study show that electric vehicles are not only an alternative transportation, but also a symbol of status and modernity. People are starting to adopt a more environmentally friendly lifestyle, encouraging the formation of communities that care about sustainability issues. However, challenges such as skepticism about product quality and concerns about losing jobs in the traditional transportation sector have also emerged, creating resistance. To overcome these challenges, public education and collaboration between government, industry, and communities are essential. With an inclusive approach, the distribution of electric vehicles can improve the quality of life of Jakartans and shape a more progressive cultural identity. This study is expected to provide new insights into the relationship between technology, culture, and society in the modern era.